Pengaruh Pemberitaan “Kasus Brigadir Yoshua” Di Media Televisi Terhadap Opini Masyarakat Kepada Kepolisian Di Perumahan OPI Kec. Jakabaring Kota Palembang - Muhammad Danil Agung PPP; Aliasan; Hasril Atieq Pohan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Journalism as a news processing technique so that it is feasible to spread it to the public. A good journalist This research is based on the reporting of the Brigadier Yoshua case. Because this will definitely raise the perception of many people regarding the "Brigadier Yoshua Case". Which was broadcast on several Indonesian Mainstream Media which involved many police officers involved in this case and made this news attract the public's attention because it was carried out by a high-ranking police officer, namely Ferdy Sambo, S,H., S.I.K., M.H. so that the researchers determined the title "The news about "Brigadier Yoshua Case" influences public opinion towards the police in the OPI Housing District, Palembang City." The aim of the research is to find out how the news about the "Brigadier Yoshua Case" influences public opinion towards the police. This type of quantitative research uses data collection techniques through questionnaires, observation and documentation. The research sample is 22 people in the Opi Jakabaring Palembang housing complex validity test, reliability test, data normality test, homogeneity test and hypothesis test. The results of the research show that the hypothesis test value ttable = db 5% 2.66 can be calculated so that tcount is 10.089 > ttable 2.66, with a sig value of 0.008 <0.05. influence. It can be concluded that the reporting of the "Brigadier Yoshua Case" has a positive and significant influence on Public Opinion towards the Police, the R square value of 0.670 (67%) is strongly related. The researcher's advice to the public is to be wiser in selecting information from existing news.